The Effectiveness of Online Learning in the Electronics Practicum Course - Rinaldi, Reza Satria; Maisarah, Ira (DPTE FT UNY, 2023)
Online learning is a new paradigm in the world of education. Not only theory in class but online learning is also carried out practical in classes. One example is in the Electronics Practicum course. However, effective online learning in practicum courses during the Covid-19 Pandemic has never been known, especially in the Electrical Engineering Study Program at the University of Bengkulu. This study aims to find the effectiveness of online learning in electronics practicum courses. The research method used is a quantitative descriptive method with a research design model using the concept of A/B design. Data was collected through a questionnaire and analyzed using the theory of effective value range. The results show that online learning in practicum courses has been effective. The results of questionnaires from students with positive scores â‰¥ 61 – 100. Thus, it can conclude that online learning for practicum courses is effective.